Pengaruh Ta'dib dan Nilai Tauhid Terhadap Disiplin Belajar Siswa di SMA IT Ittihad Makassar - Nuraeni Nuraeni; Syamsuhri Halim (Indo-MathEdu Intellectuals Journal, 2026)
Student learning discipline in Islamic schools is still a challenge, while empirical evidence regarding the influence of understanding ta'dib and internalizing the value of monotheism on learning discipline is still limited. This research aims to analyze the partial and simultaneous influence of understanding ta'dib and internalizing the value of monotheism on student learning discipline at SMA IT Ittihad Makassar. The research uses a quantitative approach with an explanatory survey design. The research population consisted of 50 students and all were sampled using total sampling techniques. Data was collected using a five-point Likert scale questionnaire which met validity and reliability tests. Data analysis was carried out through classical assumption tests and multiple linear regression. The research results show that understanding ta'dib and internalizing the value of monotheism each have a positive and significant effect on students' learning discipline. Simultaneously, the two variables also have a significant effect with the ability to explain variations in learning discipline of 30.1%. These findings indicate that strengthening understanding of ta'dib and internalizing the value of monotheism are important factors in forming student learning discipline. This research provides empirical evidence regarding the integration of Islamic education concepts with the formation of disciplinary character in the context of Integrated Islamic Schools at the high school level.